Peran Mediasi Voice Behavior dalam Komitmen Organisasi, Keterikatan Karyawan, dan Perubahan Organisasi - Juarti Juarti; Samson Laurens; Mike J Rolobessy (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study investigates how organizational commitment and employee engagement influence organizational change through the mediating role of employee voice behavior. Using a descriptive–quantitative approach with a causal–correlational framework, the research was carried out at the Regional Revenue Agency of West Seram Regency over a two-month period (April–May 2024) and involved all 35 employees through a full-sampling technique. Data were analyzed using path analysis to examine direct and indirect effects among variables. The results show that organizational commitment and employee engagement each have a positive and significant effect on employee voice behavior, while voice behavior strongly promotes organizational change, indicated by a substantial path coefficient of 0.887. In contrast, neither organizational commitment nor employee engagement has a direct impact on organizational change; their influence appears only indirectly through voice behavior, confirming a full mediation effect. These findings underscore the strategic importance of fostering a supportive climate that empowers employees to express constructive ideas, as such behavior serves as a critical mechanism for enabling organizational transformation.